PENGGUNAAN APLIKASI WHATTSHAP DALAM PEMBELAJARAN SEJARAH DI KELAS X SMA N 4 KOTA JAMBI - Hafizhah, Rahmi; Rahim, Arif (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2022)
The purpose of this study was to determine how much influence the teacher's communication had in the learning process using the WhatsApp application on the learning activities of class X students on History material at State High School 4 Jambi City. This research is a descriptive quantitative study to determine the quality of learning by using the WhatsApp application in history learning at SMA Negeri 4 Jambi City. Based on the results of research that has been done regarding the use of the WhatsApp application in history learning at SMA Negeri 4 Jambi City. Based on the data from the questionnaire results, 36 students consisted of three indicators, each of which obtained a percentage of 75.10% classified as "Effective Enough" on the indicators of learning quality. While the other indicators are indicators of student readiness in participating in learning with a percentage of 72.44% in the "Effective Enough" category. Furthermore, the last one on the student time indicator with a percentage of 71.11% is classified in the "Effective Enough" category. So it can be concluded that the use of the whatsapp application in history learning at SMA N 4 Jambi City shows an average percentage of 72.83% of indicators classified as "Effective Enough.